Estados alternativos de equilíbrio em dois lagos rasos da bacia hidrográfica do Rio Mamanguape e relação com o uso e cobertura do solo. - Alves, Rafael Machado de Araújo (2016)
The shallow lakes are susceptible to multiple impacts ecosystems, including eutrophication, often artificial, linked to population and industrial growth disorderly. The work has as i) objectives to characterize the relationship of land use and land cover with the clear waters of states and turbid in two lakes in Mamanguape Basin and ii) evaluate the effects (direct and indirect) of the abiotic variables on percentage of infestation of weeds (PVI) and biomass of phytoplankton in lakes bread and Saint Lucia. Monthly collections were carried out between January and June 2015, the biotic and abiotic variables in three sampling points in each lake. The use and land cover were determined by satellite images and visual interpretation technique. To assess the direct and indirect effects of biotic and abiotic variables in Saint Lucia and bread, we use a path analysis, partial least squares model (PLS-PM). The PAO lake remained eutrophic and low transparency as opposed to Saint Lucia, oligotrophic and clear water throughout the period. The advanced state pao eutrophication is associated with high contribution of diffuse sources of sewage, with 37.63% of its marginal area classified as urban / built, different from Lake St Lucia, in which this class occupies only 2.43%. The lakes have different alternative states, Saint Lucia with clear water and the presence of submersed aquatic and bread with turbid waters and the presence of cyanobacteria. The model presented in Saint Lucia, as the most direct influence variable in PVI and biomass of phytoplankton total phosphorus in the water followed by the total sediment phosphorus. In PAO highlight the direct effect of total phosphorus in the water phytoplankton biomass, followed by the effect of precipitation and wind speed on the photic zone and total phosphorus in the sediment, corroborating the results found, where there is more phosphorus available in the water column (181.83 μg.L-1) in the sediment (39,47 μg.g-1). These models are the generation of new hypotheses about the environments. Conservation measures and quality management are needed to preserve water resources.